The Catabase In The Greek World Between Its Past And Its Future - Bonnechere, Pierre; Cursaru, Gabriela (Etudes classiques (Namur), 2015)
DiVA portal is a finding tool for research publications and student theses written at the following 50 universities and research institutions.